Educación a adultos jóvenes sobre beneficios de la estimulación temprana. Centro de Salud Santa Rosa. Riobamba, 2019 - Isabel Antonella, Verdezoto Raza (2021)
5. ABSTRACT In the research entitled "Education of young adults on the benefits of early stimulation. Centro de Salud Santa Rosa. Riobamba, 2019, the main objective was to socialize this topic in the Centro de Salud Santa Rosa. Riobamba, 2019", type "B" with the young adults attending, topics such as the benefits of early stimulation to evaluate, improve their knowledge and in this way generate a population with knowledge and awareness focused on prevention as far as early childhood is concerned, with a population of 75 people who were surveyed and excluded according to knowledge, leaving us with a sample of 43 people. The methodology applied in the research was of a qualitative, quantitative, and longitudinal type with an applicative, explanatory, field design and the observation through which it is possible to determine the difference between knowing about the subject and its application, in which an initial and a final survey of 14 questions about early stimulation was applied. Detecting thanks to the application of the initial survey that most of the participants do not know the benefits of early stimulation. When analyzing other researches, it is clear that the main problem is that in Ecuador early stimulation is provided as a free service, for example in the health centers of the city of Riobamba, one of them is the Centro de Salud Santa Rosa. Unfortunately, the population does not know about this service or the important benefits for the correct development of the children even when they attend a health center, giving rise to a deficit of knowledge in young adults. And it is of great importance since some centers provide this service but there is not the necessary number of people prepared in this field and not all the children have the necessary resources to attend a center of these, knowing that the early age must be the stage in which the children are soaked of knowledge since 85% of the brain is developed in the first childhood. Keywords: early stimulation, prevention, promotion, development, children Reviewed by: Mgs. Hugo Romero ENGLISH PROFESSOR c.c. 0603156258